Peran Al-Qur'an Dalam Membentuk Sikap Anti-Fomo Pada Remaja - Aini Fauziyah (FKIP UNSULTRA, 2026)
This study aims to analyze the role of Qur’anic values in developing anti-Fear of Missing Out (FOMO) attitudes among adolescents in the digital era. The research employed a qualitative approach using library research and content analysis techniques based on relevant scientific journals, books, and Qur’anic exegesis. The findings indicate that FOMO is a psychological phenomenon influenced by low self-regulation, self-esteem issues, and high intensity of social media use. The study identifies five key Qur’anic values that contribute to reducing FOMO: gratitude (syukur), contentment (qana’ah), patience (sabar), trust in God (tawakal), and remembrance of God (zikir). Gratitude reduces social comparison tendencies, contentment enhances self-satisfaction, patience regulates emotional responses, tawakal provides psychological calmness, and zikir strengthens spiritual connections that foster inner peace. These five values form an integrated system of mental resilience that helps adolescents cope with digital social pressures. The findings further demonstrate that integrating Qur’anic values with contemporary psychological perspectives provides a more comprehensive framework for understanding and addressing FOMO among adolescents. Thus, the internalization of Islamic values functions not only as a religious practice but also as a psychological strategy for reducing the negative impacts of social media. The study contributes to the development of a Qur’an-based character education framework as an alternative approach to strengthening adolescent mental health and psychological resilience in the digital age.